PENGARUH KEPEMIMPINAN, MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA BIRO PENGAWASAN DAN PEMERIKSAAN PT BANK PANIN TBK - Luhur, Raden Yohanes (Operations Excellence: Journal of Applied Industrial Engineering, 2016)
Abstract. Decline in the performance of the employee’s achievement of business targets are not marked with the reporting of audit results in the last three years. This research aims to analyze the influence of leadership, work motivation and the work environment on performance of employees in Biro Pengawasan dan Pemeriksaan of PT Bank Panin Tbk. The method of research is descriptive analysis. The population of the research was the entire employees of Biro Pengawasan dan Pemeriksaan PT Bank Panin Tbk which totaled 253 people. Sampling techniques using simple random sampling with the formula slovin found 155 employees as sample. The methods analysis of this study is multiple linear regression. F test results show that leadership, work motivation and work environment has a positive and significant influence on performance of employees. The t-test results show that the leadership of significant and negative effect on performance of employees, motivation of working is not significant and negative effect on performance of employees and work environment a significant and positive effect on performance of employees. Based on the results of employees performance analysis can be maximized through increased psychological conditions of the work environment, as we reduce overtime. Keywords: Leadership, Work Motivation, Work Environment, Employees Performance.